Computer-aided identification, synthesis, and biological evaluation of novel inhibitors for botulinum neurotoxin serotype A. Issue 17 (1st September 2015) - Teng, Yu-Han Gary; Berger, William T.; Nesbitt, Natasha M.; Kumar, Kunal; Balius, Trent E.; Rizzo, Robert C.; Tonge, Peter J.; Ojima, Iwao; Swaminathan, Subramanyam
Graphical abstract: Abstract: Botulinum neurotoxins (BoNTs) are among the most potent biological toxin known to humans, and are classified as Category A bioterrorism agents by the Centers for Disease Control and prevention (CDC). There are seven known BoNT serotypes (A–G) which have been thus far identified in literature. BoNTs have been shown to block neurotransmitter release by cleaving proteins of the soluble NSF attachment protein receptor (SNARE) complex. Disruption of the SNARE complex precludes motor neuron failure which ultimately results in flaccid paralysis in humans and animals. Currently, there are no effective therapeutic treatments against the neurotoxin light chain (LC) after translocation into the cytosols of motor neurons. In this work, high-throughput in silico screening was employed to screen a library of commercially available compounds from ZINC database against BoNT/A-LC. Among the hit compounds from the in silico screening, two lead compounds were identified and found to have potent inhibitory activity against BoNT/A-LC in vitro, as well as in Neuro-2a cells. A few analogs of the lead compounds were synthesized and their potency examined. One of these analogs showed an enhanced activity than the lead compounds.